Cross-cultural design. applications in cultural heritage, creativity and social development : 10th International Conference, CCD 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: applications in cultural heritage, creativity and social development : 10th International Conference, CCD 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available